Writing as a Dynamic Endeavor - Carlo Granados; Imelda Zorro (Asociación Colombiana de Profesores de Ingles, 2016)
This paper attempts to facilitate assessing undergraduate students' progress and teachers' work in academic writing. A progress chart has been used to provide feedback to the learners and for them to self-evaluate their work. Drafting, revising and editing are conducted for both the teacher and the student to keep track of the learners' difficulties. A portfolio showing on-going feedback as well as treatment, suggestions and tips for improving writing hope to overcome learner's difficulties.